BERBAGI PENGETAHUAN SEBAGAI ALTERNATIF PENCIPTAANPENGETAHUAN UNTUK STAF PENGAJAR VOKASI UI - Safitri, Dyah (Jurnal Vokasi Indonesia, 2013)
The process of knowledge sharing becomes important processes for an organization in creating new knowledge and innovation. Tacit and explicit knowledge can be moved through several processes to knowledge sharing. Culture an important part of the process, especially an appreciation of the sources of knowledge that is willing to share the knowledge. In educational organizations especially recently established such as Vocational Program UI should institutionalization of knowledge as a knowledge center will be beneficial in the process of knowledge sharing.